2018
DOI: 10.1186/s13104-018-3489-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of diabetes self-care practice and associated factors among type two adult diabetic patients following at public Hospitals in central zone, Tigray Region, Ethiopia, 2017

Abstract: ObjectiveSelf-care practice in type two diabetes is a critical factor to keep the disease under control. Despite the important role of self-care practices in management of diabetes were recognized to be useful and effective in achieving diabetes control and preventing its complication, findings of previous studies in Ethiopia were confirmed that, aspects of self-care practices were more problematic. So that this study focus on magnitude of self-care practice and associated factors among diabetic patients.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
45
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 12 publications
21
45
3
1
Order By: Relevance
“…Of the included studies, studies from Diredawa (7), Oromia (11), Addis Ababa (8), and Amhara (25) regions have shown a significant association; patients who had good knowledge about diabetics were good at applying self-care practice. However, a study conducted in the Tigray region did not show an association (34).…”
Section: Determinants Of Diabetics' Self-care Practicementioning
confidence: 89%
See 4 more Smart Citations
“…Of the included studies, studies from Diredawa (7), Oromia (11), Addis Ababa (8), and Amhara (25) regions have shown a significant association; patients who had good knowledge about diabetics were good at applying self-care practice. However, a study conducted in the Tigray region did not show an association (34).…”
Section: Determinants Of Diabetics' Self-care Practicementioning
confidence: 89%
“…Southern Nations Nationalities and Peoples (SNNPs) (10,32), Tigray (33,34), and Addis Abeba (8,35) each contributed two articles to the review. While the remaining study was from Benishangul Gumuz region (36).…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%
See 3 more Smart Citations